Hospital Waste Management through Green QFD Implementation - Rudy Joegijantoro (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2020)
Based on case studies conducted in various health institutions, the high production of medical waste is one proof that medical waste management is still problematic. This study examines various problems in the field of medical waste management. This study explores staff perceptions of medical waste management. This study aims to determine the level of knowledge and attitudes as well as the role of health workers on medical waste management. Here we study the quality index and environmental index of two health care centers, one is a private hospital and one is a government hospital and compared these two indices with each other via a questionnaire survey. To produce more environmentally friendly services, customers, and environmental criteria must be considered during the decision-making process, and the Implementation of Green QFD (G-QFD) provides a very useful methodology to meet this goal.